On the Xantholinini of Turkey and adjacent regions (Coleoptera: Staphylinidae: Staphylininae) - Assing, Volker (Zootaxa, 2007)
Based on a study of types and additional material, 11 species of Xantholinini from the Eastern Mediterranean are (re-)described and illustrated, 8 of them as new: Vulda ottomana (Cameron, 1912), V. cangalica sp. n. (Turkey: Sinop), Xantholinus (Typhlolinus) gridellii Coiffait, 1956, X. (Calolinus) puthzi Bordoni, 1979, X. (C.) ibex sp. n. (Turkey: Muğla, Antalya), X. (C.) marasicus sp. n. (Turkey: Kahramanmaraş), X. (C.) penicillatus sp. n. (Turkey: Muğla, Konya), X. (Helicophallus) multispinosus sp. n. (Turkey: Mersin), X. (H.) brevispinosus sp. n. (Turkey: Antalya), X. (H.) bitlisicus sp. n. (Turkey: Bitlis), and X. (H.) chersonesicus sp. n. (Turkey: Çanakkale). The male sexual characters of 6 additional species are illustrated. The following synonymies are proposed: Megalinus Mulsant & Rey, 1877 = Leptophius Coiffait, 1983, syn. n.; Vulda ottomana (Cameron, 1912) = Xantholinus anatolicus Coiffait, 1965, syn. n.; Xantholinus reitteri Coiffait, 1966 = X. svanetskiensis Coiffait, 1973, syn. n., = X. motschulskyi Bordoni, 1999, syn. n.; X. rufipennis Erichson, 1839 = X. phenicius Coiffait, 1971, syn. n.; X. nicolasi Coiffait, 1972 = X. pantokratoris Bordoni, 1975, syn. n.; X. crassicornis Hochhuth, 1851 = X. lederi Coiffait, 1966, syn. n., = X. martensi Bordoni, 1983, syn. n., Megalinus scutellaris (Fauvel, 1900) = Lepidophallus denticulatus Bordoni, 2004, syn. n. Lectotypes are designated for Xantholinus motschulskyi Bordoni, X. rufipennis Erichson, and X. procerus Erichson, 1839. The binomen Megalinus flavocinctus (Hochhuth, 1849), comb. n. (ex Leptophius) is established. Numerous additional records of Xantholinini are reported from the Eastern Mediterranean and adjacent regions, among them first country records from Turkey (5 species), Greece (2 species), Bosnia-Herzegovina (1 species), Albania (1 species), Jordan (1 species), Israel (5 species), Georgia (2 species), Azerbaijan (2 species), Turkmenistan (1 species), and Iran (3 species). An annotated checklist of the species of Xantholinini recorded from Turkey is compiled. The distributions of 23 species are mapped; the distribution of X. procerus is discussed. Vulda ottomana is the first example of a Vulda species with a pronounced dimorphism of the wings (elytra and hind wings), head shape, and eye size.